Patterns of systemic problems in Ghana's poultry value chain: A group model building approach - Aboah, Joshua; Enahoro, Dolapo K.; Mensah, Charles; Agyemang, Nana Adwoa; Kondo, E.; Ayertey, D. (Elsevier, 2025)
Ghana's poultry sector faces different interrelated systemic challenges, often diagnosed in isolation, leading to interventions that neglect unintended consequences across the value chain. Consequently, a holistic prognosis of the impact of these systemic problems that considers the different facets of the poultry industry is required. This paper aims to examine the system archetypes emerging from the inherent industry-level and farm-level problems in Ghana's poultry sector. Adopting a participatory group model building process, causal loop diagrams and feedback loop analyses were applied to understand the interacting factors in four systemic problems prioritised by stakeholders in Ghana's poultry value chain. Four causal loop diagrams were mapped for these systemic problems; (i) inadequate research funding (ii) low adherence to biosecurity measures at the farm level; (iii) lack of access to credit; and (iv) the competition from cheap imports of poultry meat products. The findings highlight three emerging problem archetypes. First, the underachievement archetype, specifically the limit to growth, emerges when technology adoption due to increased research funding interacts with the non-adherence to biosecurity measures as a cost-cutting strategy at the farm level. Second, the out-of-control archetype emerges when the misuse of antimicrobials due to the non-adherence of biosecurity measures interacts with the industry's collapse and the consequential surge in chicken imports into the country. Third, the relative achievement archetype emerges from the reinforcing feedback loop which centres around the surge in imported chicken as a response to looming food insecurity concerns arising from insufficient domestic supply. The “success to the successful” archetype is thus created, where importers in the poultry value chain become more prosperous at the expense of the entire industry. The paper presents solutions to the emerging problem archetypes, providing stakeholders with a chance to evaluate the unintended consequences of proposed government policies aimed at rejuvenating local poultry production.